The power of your subconscious mind - Murphy, Joseph 1898-1981 (Reward Books, 2000)
Dr. Murphy's revolutionary mind-focusing techniques are based upon a proven and entirely practical principle: If you believe in something without reservation and picture it in your mind, you remove the subconscious obstacles that prevent you from achieving that end results, and your belief becomes a reality.